Understanding and practicing crisis consulting: A study of public relations and communications firms. Issue 2 (2nd May 2017) - Johansen, Winni
Abstract : Purpose: The purpose of this paper is to contribute to the literature on management and communication consulting in general, and crisis consulting in particular, by investigating how public relations and communications firms understand crises, crisis management, and crisis communication; how they see themselves practicing crisis consulting; and how they envisage the future of this field of expertise. Design/methodology/approach: The study is based on 12 semi-structured in-depth expert interviews with CEOs, board members, senior consultants, and/or partners representing national and international public relations and communications firms operating in Denmark who offer crisis consulting as one of their areas of expertise. Findings: Findings demonstrate that crisis consulting is a field in transition, moving away from the traditional focus on image crises in the media handled by former journalists, toward a new focus on issue crises involving other types of stakeholders. Findings also demonstrate that crisis consultants generate important insights into aspects of crisis management and crisis communication hitherto neglected by academic scholars. Practical implications: The insights into the professional "world view" of crisis consultants will contribute to the professionalization of the field. Originality/value: This is the first major study of crisis consulting as a specific field of expertise within the growing industry of management and communication consulting.